772. Factors Associated With Healthcare Delay of Active Pulmonary Tuberculosis After Hospitalization. (26th November 2018) - Han, Jaijun; Park, Se Yoon; Park, Jebyung; Lee, So Young; Kim, Gil Eun; Jeong, Yeon Su; Kim, Jin Hwa; Lee, Eunyoung; Lee, Eun Jung; Yu, Shi Nae; Kim, Tark; Jeon, Min Hyok; et al.
Abstract: Background: Hospitals are undesirable reservoirs for a respiratory outbreak. Active pulmonary tuberculosis (TB) can be readily transmitted among hospitalized patients. Early recognition of pulmonary TB is an essential priority against transmission. The aim of this study was to evaluate factors associated with delayed identification of pulmonary TB in hospital settings. Methods: Medical records of newly diagnosed TB patients admitted to a referral hospital from January 2015 through December 2017 were reviewed. Delayed recognition of pulmonary TB was defined as failure to initiate airborne isolation within the first 3 days after admission. We analyzed clinical, microbiological, radiological, and healthcare factors associated with delayed recognition of pulmonary TB. Patients who were not suspected of having active pulmonary TB had no remarks about TB on their initial chest radiograph interpretation by radiologists. Multivariate logistic regression analysis was performed with significant factors included. Results: A total of 136 patients were analyzed who had positive sputum acid-fast bacilli (AFB) cultures. Of these, 45 (33%) patients were isolated 3 days after admission and had longer days of exposure before isolation (median 9, interquartile range [IQR] 6–14, P < 0.001) in comparison to others (median 0, IQR 0–1). Patients with older age (odds ratio [OR] = 1.04, 95% confidence interval [CI] 1.01–1.08, P = 0.01), patients who were admitted to departments other than infectious diseases or pulmonology (OR = 6.23, 95% CI 2.17–17.89, P = 0.001) and patients who were not suspected of having active pulmonary TB by radiologists (OR = 11.36, 95% CI 4.11–31.39, P < 0.001) were more likely to have delayed recognition of pulmonary TB. Conclusion: In a country with intermediate TB prevalence, better awareness for pulmonary TB is required for all hospitalized patients who are admitted to departments other than infectious diseases or pulmonology. Although active pulmonary TB is not suspected by a radiologist, sputum AFB smear, and culture are necessary when new lesions are present in chest radiographs. Disclosures: All authors: No reported disclosures.